Preventive role of Pastinaca sativa in mitigating metabolic dysfunction-associated steatotic liver disease via modulation of metabolic endotoxemia - Ji-Eun Park; Hye-Bin Lee; Yu Ra Lee; Guijae Yoo; Hee-Kyoung Son; Sang Yoon Choi; Miri Park; Ho-Young Park (npj Science of Food)
Abstract Metabolic dysfunction-associated steatotic liver disease (MASLD) is a leading global liver disorder. Parsnip (Pastinaca sativa), rich in dietary fiber and medicinal properties, has shown health benefits, but its effects on MASLD are largely unexplored. This study evaluated the prebiotic and anti-MASLD effects of parsnip root water-soluble extract (PRE) in a mouse model. Mice fed a high-fat diet with 50 or 100 mg/kg PRE for eight weeks showed reduced fat accumulation, improved serum metabolic profiles, and decreased liver injury markers. PRE also lowered hepatic lipogenic protein levels induced by the high-fat diet. Additionally, PRE enhanced gut health by reducing endotoxins, improving intestinal permeability, and upregulating tight junction proteins. These results indicate that PRE can improve gut health, prevent MASLD, and support its potential as a dietary supplement to enhance metabolic health.